Evaluation of treatment and recovery of leachate by bipolar membrane electrodialysis process - Ilhan, F.; Kabuk, H. A.; Kurt, U.; Avsar, Y.; Sari, H.; Gonullu, M. T. (ELSEVIER SCIENCE SA, 2014)
Recovery studies are frequently carried out for electrodialysis (ED) processes. In this study, beyond examining the recovery of leachate components in an electrodialysis process, the use of that process to treat leachate-containing wastewater was simultaneously tested. Leachates were initially pre-treated (ultra filtration + cation exchange) to prevent clogging' and harmful effect to the bipolar electrodialysis membranes. Optimum operating conditions were determined at the end of the experimental studies. Online observations during the electrodialysis process included the temperature-dependent reaction time, conductivity and changes of molar concentrations of H+ and OH- ions in both the anolyte and catholyte compartments in which removed ions were collected. The most important contaminants in leachates are organic substances and nitrogen compounds. For this reason, representations of organic substances, such as the chemical oxygen demand (COD), and nitrogenous compounds, such as total Kheldahl nitrogen (TKN) and ammonia-nitrogen (NH3-N), were also monitored in the electrodialysis effluent. Under the optimum operating conditions, removal of NH3-N, TKN and COD were determined in the effluent at 96.2%, 92.8% and 86.7%, respectively. The conductivity value was determined to be 1.97 mS/cm at the end of the study. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Electrodialysis; Bipolar membrane; Leachate; Recovery; ORGANIC-ACIDS; WASTE-WATER; EXCHANGE; FEASIBILITY; Energy & Fuels; Engineering